2016
DOI: 10.1017/idm.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Australian Employee Perspectives on Disability Management in Relation to Job Satisfaction, Physical and Mental Health, Workplace Morale and Reduced Sickness Absence

Abstract: Disability management is now recognised as an effective means of managing the increasing global costs of injury and disability. However, research on disability management particularly employee perceptions of its value, are sparse. This paper reports on the Australian findings of a large international project that included Canada, China, Switzerland and Australia, which examined employee perspectives of disability management related to job satisfaction, physical and mental health, workplace morale and reduced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Eleven studies [2636] were identified that explored injured worker perspectives on key social factors that influenced their RTW process. Eight of these studies [29, 30, 32–37] reported the presence of social facilitators, while nine reported social barriers.…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven studies [2636] were identified that explored injured worker perspectives on key social factors that influenced their RTW process. Eight of these studies [29, 30, 32–37] reported the presence of social facilitators, while nine reported social barriers.…”
Section: Reviewmentioning
confidence: 99%
“…Regular contact and good communication with the employer was identified as a facilitator of RTW in two medium quality studies [29, 34]. In four medium quality studies, supervisor communication was found to be most important for injured workers’ expectations of the RTW process, and in assisting with the worker's informational and practical RTW needs [29, 32, 36, 37]. Being able to discuss the injury or illness was also found to be important when communicating with co-workers in one medium quality study [30].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations